You’re It—You’ve Got to Save Someone: Immediate Responders, Not Bystanders - Ashkenazi, Isaac; Hunt, Richard C. (Frontiers in Public Health, 2019)
Recurring disasters and life-threatening emergencies mandate that communities across the world be adequately prepared to prevent, respond, and recover from these events. Experiences throughout the world with mass casualty incidents and other disasters have increasingly highlighted the vital role that “active bystanders”—persons at the scene of an event who step forward to help—can play in preventing, containing, reporting, saving lives, decreasing morbidity, and increasing resilience. This paper seeks to emphasize the importance of the public in response to emergencies. No longer should we use the passive word “bystanders.” Rather immediate responders fill a critical silent gap before trained professionals arrive. In support of immediate responders this paper will identify the barriers to bystander action, and provide next steps to increase the number of individuals who take action at times of emergency. Immediate responders can and do play a valuable and unique role in reducing mortality, morbidity, and suffering from emergency events. While some cultures and countries have a long history of engaging the public as critical in an emergency response, others do not. The challenge is how best to increase the number of individuals who are motivated, prepared and ready to respond appropriately when they find themselves at the scene of an active shooter, bombing, hurricane, earthquake, tornado, fire, vehicle crash, or other life-threatening emergency.